2005
DOI: 10.14490/jjss.35.205
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Analysis of a Markov Switching Stochastic Volatility Model

Abstract: This article analyzes a Markov switching stochastic volatility (MSSV) model to accommodate the shift in the mean of log-volatility. Since it is difficult to estimate the parameters in this model based on the maximum likelihood method, a Bayesian Markov-chain Monte Carlo (MCMC) approach is adopted. A particle filter for the MSSV model, which is used for model comparison and diagnostics, is constructed. The estimation result, based on weekly returns of the TOPIX, confirms the finding by previous researchers that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
(45 reference statements)
1
6
0
Order By: Relevance
“…For instance, in this paper the estimated volatility of financial asset return changes does not accommodate sudden structural breaks. Recently, the SV model with jumps (Barndorff-Nielsen and Shephard, 2001; Chib et al, 2002) and the regime switching models (So et al, 1998; Shibata and Watanabe, 2005; Abanto-Valle et al, 2009) have received considerable attention. The volatility of daily stock index returns has been estimated with SV models but usually results have relied on extensive pre-modeling of these series, thus avoiding the problem of simultaneous estimation of the mean and variance.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in this paper the estimated volatility of financial asset return changes does not accommodate sudden structural breaks. Recently, the SV model with jumps (Barndorff-Nielsen and Shephard, 2001; Chib et al, 2002) and the regime switching models (So et al, 1998; Shibata and Watanabe, 2005; Abanto-Valle et al, 2009) have received considerable attention. The volatility of daily stock index returns has been estimated with SV models but usually results have relied on extensive pre-modeling of these series, thus avoiding the problem of simultaneous estimation of the mean and variance.…”
Section: Discussionmentioning
confidence: 99%
“…According to the CD values, the null hypothesis that the sequence of 50 000 draws is stationary is accepted at the 5% level for all the parameters in all the models considered here. [13,24,35]. On the other hand, the posterior mean and the 95% interval of 2 are 0.1456 and (0.1010, 0.2080), which are higher than the 0.0588 and (0.0353, 0.0940) in the SV model and the 0.0641 and (0.0388, 0.0971) in the SVt model.…”
Section: Empirical Applicationmentioning
confidence: 77%
“…Multi-move samplers have been used to update the log-volatilities. For example, So et al [13] use the mixture sampler Gibbs sampling [18,24] the block sampler Gibbs sampling [25,26].…”
Section: Mssv-vol Model Estimation Using Mcmcmentioning
confidence: 99%
“…The volatility of the S&P500 index is in the high regime during the years 1999-2001 (could be attributed to the dot-com bubble) and 2008-2010 (financial crisis). Table 3 presents the estimated parameter means and [32][33][34][35] among others). Table 4 presents the LPS, LPTS , and LPBF for the S&P500 data.…”
Section: Real Data Applicationmentioning
confidence: 99%
“…Kalimipalli and Susmel 34 considered two-factor SV model with regime switching and found that the estimated high volatility persistence is reduced when the regimes are incorporated in the model. Shibata and Watanabe 35 also found that the persistence parameter estimates drop as compared to those of the standard SV models. Moreover, for their data, the MSSV model performs better than the benchmark SV models.…”
mentioning
confidence: 91%